(untitled) (World Bulletin of Management and Law, 2023)
Various scientific debates are taking place today not only at the national level but also within the framework of international organizations on the role of countries, international organizations on issues of legal regulation of foreign citizens’ activities, foreign labor migration and its legal regulation. The main reason for this is sharp increase of labor migration process in the world in recent years, growing aspirations of foreign citizens in carrying out activities in other countries, as well as involvement of foreign professionals in working in other countries as the result of attracting foreign investment, signing bilateral agreements of employment on the basis of the principle of reciprocity between the two states. Bringing national legislation on human rights in accordance with international standards, development of foreign economic activity of enterprises and organizations entail the emergence and increase of labor relations with so-called foreign element. Based on this, in this article, different aspects of collision-legal regulation of labor relations with complicated foreign element are covered and analyzed. In this, the author pays attention to the types and importance of collision norms governing international labor relations, as well as the principle of autonomous will as a method of collision-legal regulation of labor relations.